2010
DOI: 10.2169/internalmedicine.49.3831
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Type 1 Diabetes Onset and Recurrence of Graves' Disease During Pegylated Interferon-Alpha Plus Ribavirin Treatment for Chronic Hepatitis C

Abstract: We report a case of type 1 diabetes onset and recurrence of Graves' disease during pegylated interferon (PEG-IFN)-alpha plus ribavirin treatment for chronic hepatitis C. The patient was a 55-year-old woman diagnosed with chronic hepatitis at age 46 years. She was treated for Graves' disease at 50 years of age. Because Graves' disease remitted, PEG-IFN-alpha plus ribavirin treatment was started for chronic hepatitis C. She was examined because of complaints of general fatigue, weight loss, and palpitations afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
0
15
0
1
Order By: Relevance
“…We reviewed the data for each of these cases, focusing on the length of time from the start of IFN+RBV therapy to the onset of type 1 diabetes mellitus, continuation/ discontinuation of IFN therapy after the onset of type 1 diabetes, weaning/nonweaning from insulin therapy after discontinuation of IFN+RBV, presence/absence of pancreas-associated autoantibodies before and after IFN+RBV therapy, and the HLA haplotype of the patients (Table 1). While in most cases IFN+RBV therapy had been discontinued immediately after the diagnosis of type 1 diabetes,3,816,18,2024 the treatment had been continued in two cases, including the present case 25. Insulin therapy could be discontinued later in only two of the 19 cases in which IFN+RBV therapy had been stopped immediately after the diagnosis of type 1 diabetes 8,23.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We reviewed the data for each of these cases, focusing on the length of time from the start of IFN+RBV therapy to the onset of type 1 diabetes mellitus, continuation/ discontinuation of IFN therapy after the onset of type 1 diabetes, weaning/nonweaning from insulin therapy after discontinuation of IFN+RBV, presence/absence of pancreas-associated autoantibodies before and after IFN+RBV therapy, and the HLA haplotype of the patients (Table 1). While in most cases IFN+RBV therapy had been discontinued immediately after the diagnosis of type 1 diabetes,3,816,18,2024 the treatment had been continued in two cases, including the present case 25. Insulin therapy could be discontinued later in only two of the 19 cases in which IFN+RBV therapy had been stopped immediately after the diagnosis of type 1 diabetes 8,23.…”
Section: Discussionmentioning
confidence: 73%
“…Twenty-eight cases of type 1 diabetes mellitus diagnosed after the start of IFN+RBV therapy have thus far been reported in the English language literature 3,825. We reviewed the data for each of these cases, focusing on the length of time from the start of IFN+RBV therapy to the onset of type 1 diabetes mellitus, continuation/ discontinuation of IFN therapy after the onset of type 1 diabetes, weaning/nonweaning from insulin therapy after discontinuation of IFN+RBV, presence/absence of pancreas-associated autoantibodies before and after IFN+RBV therapy, and the HLA haplotype of the patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes prone BB rats and mice treated with streptozotocin had expression of type I interferon in their pancreatic islets [40]. There are reports of patients treated with type I interferon for chronic viral infections that then developed diabetes [41]. In the case of mice, enforced expression of type I interferon in islets caused autoimmune diabetes [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IFN-α can cause an immune response shift to T-helper-1-type predominance and alter the expression of histocompatibility class I and II antigens, possibly leading to the development of VKH disease [5, 8]. In addition, administration of IFN-α may lead to the development of VKH disease via an increase in the production of endogenous IFN-α, and it has been reported that serum endogenous IFN-α titers are significantly elevated in VKH disease patients [9, 10].…”
Section: Discussionmentioning
confidence: 99%